DIGITAL MEDIA ACCESS: FOLKLORE LEARNING FOR CULTIVATING LOVE INDONESIAN CULTURE CHARACTER - Riche Cynthia Johan; Isah Cahyani; Yudi Wibisono (Faculty of Languages and Arts, Universitas Negeri Yogyakarta, 2021)
Growing the character of love traditional culture needs to be done from the early age, in the midst of the development of technology and the global culture which have allegedly shifted traditional culture. Learning activities at primary education must provide easy access to continue to love and realize the ownership of the wealth of traditional culture, which can be pursued through the use of technology. The problems of this research are, first, whether techers could determine the subject, basic competencies, and indicators that taught about literary works to introduce culture and character; and second, what learning media was widely used by teachers in teaching literary works especially folklore. An online survey was conducted on 15 teachers teaching at primary level in West Java Province, which include Majalengka, Tasikmalaya, Garut, Ciamis, Cirebon, West Bandung, Bandung, and Sukabumi regions. This research found that first, basic competencies indicators for folklore materials in the curriculum of Bahasa Indonesia subject at elementary school/madrasa had already been included at every grade level. Second, the basic competencies were included in Bahasa Indonesia, English, Sundanese, and Cultural Arts subjects at junior secondary level. Third, the learning media supporting folklore consisted of digital media (46.7%) and printed media (86.7%) which indicated that the learning media that was often accessed for the achievement of basic competencies at each grade level to cultivate the character of love Indonesian culture was printed media.